Sensemaking of Sustainable Invesment: Fintech’s Role Shaping Retail Investor’s Green Intention in Indonesia - Ni Luh Laksmi Rahmantari; I Gusti Ayu Lia Yasmita; Made Mulia Handayani (LPPM STIE KRAKATAU, 2026)
This study examines retail investors’ intentions to invest in sustainable financial products through fintech in Indonesia, focusing on green values, digital appeal, and social interaction amid limited ESG understanding. The study applies Interpretative Phenomenological Analysis (IPA) with 15 investors, using semi-structured interviews and thematic analysis based on Sensemaking Theory. Investment intention is driven by moral motivation, digital cues, and social influence, with investors relying more on perceived plausibility than factual verification. Fintech also serves as a space for the construction of collective meaning. Fintech functions not only as a transactional tool but also as a platform that shapes perceptions of sustainable investment, highlighting the need for stronger ESG literacy, transparency, and regulation. The qualitative approach and small sample size limit the generalizability of the findings. This study offers deeper insights into investor behavior in fintech-based sustainable finance and provides practical implications for reducing greenwashing and improving authentic sustainable investment practices.